Polyurethane foam functionalized with an AIE-active polymer using an ultrasonication-assisted method: preparation and application for the detection of explosives. Issue 32 (14th March 2016) - Fan, Zhu-Xin; Zhao, Qing-Hua; Wang, Shi; Bai, Yu; Wang, Pei-Pei; Li, Jin-Jin; Chu, Zhi-Wei; Chen, Guo-Hua
Abstract : We have fabricated PU foams modified with AIE-active polymerPSiTPE nanoparticles on the flexible sponge surface. The as-prepared foams show a high sensitive to PA solution and DNT vapor. Abstract : PU foams modified with an AIE-active polymer (PSiTPE ) with a Si–O and TPE backbone using an ultrasonication-assisted method have been prepared. The as-prepared foams show a high sensitive to PA solution and DNT vapor. Moreover, it could be re-used several times. It is a novel promising probe for the detection of explosives.